KARAKTERISTIK FOULING DAN POLARISASI KONSENTRASI PADA PROSES PEMURNIAN DAN PEMEKATAN KARAGINAN DENGAN MEMBRAN MIKROFILTRASI - Uju, Linawati Hardjito, Suprihatin, Prayoga Suryadarma, dan Erliza Noor (Jurnal Teknologi Industri Pertanian, 2008)
ABSTRACTThe fouling resistance at cross flow velocity 2,97, 3,47 and 3,97 m s-1was 0,1312; 0,1741 and 0,1758 kPa m2 h l- 1 respectively.  It is not influenced by cross flow velocity and  has 2-3 times greater than internal membrane resistance. Concentration polarization resistance at range cross flow velocity 2,97 to 3,97 m s-1  was 0,4030 to 0,9314 kPa m2 h l-1. Concentration polarization resistance is influenced by cross flow velocity, where at high cross flow velocity the concentration polarization can be reduced.  At low transmembrane pressure, total resistance is dominated by fouling resistance but at high transmembrane pressure it is dominated by concentration polarization resistance.   Behavior of flux during carrageenan purification can be described finely by resistance in series model.Keywords :  carrageenan, concentration polarization, fouling, microfiltration